PENGARUH PERTUMBUHAN PENDUDUK TERHADAP PERUBAHAN PENGGUNAAN LAHAN PERMUKIMAN DI KOTA PEKANBARU TAHUN 2008-2018 - Afriani, Tari; Iskarni, Paus (JURNAL BUANA, 2024)
This study aims to determine (1) population growth in the city of Pekanbaru in 2008-2018, (2) changes in land use for settlements in the city of Pekanbaru in 2008-2018, (3) the effect of population growth on the area of ​​land use changes for settlements in the city of Pekanbaru. . This type of research is qualitative with two variables, namely population growth in Pekanbaru City, changes in land use for settlements in Pekanbaru City. The results of the study show that (1) the population growth of Pekanbaru City has experienced ups and downs every year. Based on the results of the analysis using the exponential equation, the average population growth rate in Pekanbaru City is 3.30% in the 2008-2018 period. (2) In the period 2008-2018, the area of ​​residential land has increased every year due to increasing population growth. The highest residential land area was in 2018 with an area of ​​15088.58 Ha. Meanwhile, the smallest residential land area was in 2009 with a residential area of ​​13076.88 Ha. (3) The population growth of Pekanbaru City has an influence on changes in Settlement land use. The results of the Peaerson product moment correlation obtained a large significance of 0.000. The results of the simple linear regression test obtained the equation Y = 12755.453 + 643.653X.